A comparative analysis of global cropping systems models and maps - Anderson, Weston; You, Liangzhi; Wood, Stanley; Wood-Sichra, Ulrike; Wu, Wen-Bin (International Food Policy Research Institute, 2014)
This study aims to explore and quantify systematic similarities and differences between four major global cropping systems products: the dataset of monthly irrigated and rainfed crop areas around the year 2000 (MIRCA2000), the spatial production allocation model (SPAM), the global agroecological zone (GAEZ) dataset, and the M3 dataset developed by Monfreda, Ramankutty, and Foley. The analysis explores not only the final cropping systems maps but also the interdependencies of each product, methodological differences, and modeling assumptions, which will provide users with information vital for discerning between datasets in selecting a product appropriate for each intended application.